PHARMACEUTICAL LEGISLATION OR PHARMACEUTICAL LAW? ANALYSIS - del CASTILLO Rodríguez, Carlos (Vitae, 2011)
After legal enaltment in the pharmaceutical profession appear two intimately related concepts: the pharmaceutical law andt the pharmaceutical legislation that we should define and analyze. On the one hand, the pharmaceutical law is a heterogeneous group of dispositions regulating directly or indirectly the pharmaceutical activity. It cannot be considered an independent branch of the law, but it is possible for practical effects to order systematically the legal regulations. Such is the source of a new branch inside the sanitary law, the pharmaceutical legislation, that every pharmacies most know in applied to his scientific-professional activity which evolution is vertiginous. This paper will study this concept. From the beginning this study requires the most appropriate methodological tools. The most important one for investigation must be the desire to mark out the treated topics guided by the necessary documentation. The use methodology is the usually followed in the works of pharmaceutical legislation where the primary source is found in the diverse official bulletins publishing the legal disposition and the critical literature of the topics.